Strategi Peningkatan Literasi Digital dalam Pembelajaran PABP dengan Menggunakan Google Dokumen - Aziz, Sofyan (Jurnal Didaktika Pendidikan Dasar, 2023)
Study aims to utilize Google Docs media to improve learning, students' creativity, as well as improve students’ literacy skills. By using this application, besides being easy to use, it is also expected to be able to ignite the creativity of students in working on worksheets together. This research is also to find out efforts to improve students' digital literacy skills in the subjects of Religious Education and Character Education at the Junior High School level. The benefits of this research are to improve the digital literacy skills of students. The research method used is naturalistic qualitative method to examine the factual conditions and needs of students for the development of learning designs. The research includes program design, implementation, efforts to overcome obstacles that occur in the field, and evaluation. The research instrument used observation, interview, questionnaire, and documentation techniques. This research was conducted at Junior High School 1 Sarang with the research subjects being 32 students of class 8E. Technically, the implementation procedure includes the following steps: (1) Preparing worksheets; (2) Division of tasks for students; (3) Looking for answers by using literacy resources; (4) Write down the results of the search for answers; (5) Editing the answer results into a complete reading; (6) Evaluation. From the results of the study, it was found that students were motivated to use media in learning, and the enthusiasm for learning began to grow.